Trade and the American Dream : A Social History of Postwar Trade Policy - Aaronson, Susan A. (Book collections on Project MUSE., 1996)
In Trade and the American Dream, Susan Aaronson highlights a previously ignored dimension of United States trade policy: public understanding. Focusing on the debate over the three mechanisms designed to govern world trade - the International Trade Organization (ITO), the General Agreement on Tariffs and Trade (GATT), and the World Trade Organization (WTO) - she examines how policymakers communicate and how the public comprehends trade policy. As "the American century" draws to a close, the message is clear: the American public's aspirations - indeed, the traditional pursuit of the American Dream - should be reflected in international trade policy. Aaronson suggests ways to create greater public understanding for the GATT/WTO and international trade as America enters the twenty-first century. If national trade policy is to play in Peoria, Americans must first understand it.